2017
DOI: 10.21037/tp.2017.04.02
|View full text |Cite
|
Sign up to set email alerts
|

A case of Raoultella planticola causing a urinary tract infection in a pediatric patient

Abstract: () is an abundant environmental bacterium that rarely infects humans. There is only one known case of causing a urinary tract infection (UTI) in a pediatric patient. This is a second case of potentially causing a symptomatic UTI in a 2-month-old female child with no known medical problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…In this report, the literature was also reviewed for any case reports about Raoultella planticola , and all case reports found were reviewed [[5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38]]. Pediatric cases are summarized in Table 1 [[5], [6], [7], [8], [9]]. For each case, we show the type of antibiotics used and the duration for each course, in addition to the clinical sequalae for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, the literature was also reviewed for any case reports about Raoultella planticola , and all case reports found were reviewed [[5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38]]. Pediatric cases are summarized in Table 1 [[5], [6], [7], [8], [9]]. For each case, we show the type of antibiotics used and the duration for each course, in addition to the clinical sequalae for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…One retrospective study found that 56% of the patients with a UTI due to R planticola were immunodeficient; 28% of these being solid organ transplant recipients . Additionally, most case reports describe R planticola as pan‐sensitive to most antimicrobial options including penicillins and cephalosporins, with the reports of resistance describing non‐susceptibility to ampicillin and piperacillin . These case reports of UTI due to R planticola describe successful treatment with agents such as ceftriaxone, ciprofloxacin, cephalexin, and ampicillin/sulbactam.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 29 cases of human infection with R planticola has been reported with only 3 urinary tract infections. 3 , 4 R planticola is difficult to isolate and to identify, as it can easily be confused with other genera, especially klebsiella. 5 R planticola rarely cause infection in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 cases of urinary tract infection secondary to R planticola have been reported, 1 in a pediatric patient and 2 in adults. 3 , 4 In this article, we present a case of R planticola urinary tract infection in 65-year-old male with immunoglobulin A nephropathy.…”
Section: Introductionmentioning
confidence: 99%